Hospitality and Tourism Innovation, Invention and Creativity Competition : Book of Abstracts - Saiful Bakhtiar, Mohd Faeez (Faculty of Hotel and Tourism Management, 2022)
With the hospitality and tourism market saturated and competitive, combined with the rapidly advancing technology, customers can now easily access products/services from all over the world. Providing top quality products and excellent services can no longer guarantee success and sustainability. The market situation requires constant creation and supply of innovative products and services.